Analisis Penggunaan Transformator Sisipan Untuk Mengatasi Rugi Tegangan dan Pembebanan Lebih - Rachmat Sutjipto; Heri Sungkowo; Epiwardi; Dhimas Dhesah Kharisma (Politeknik Negeri Malang, 2023)
On the JD267 distribution transformer with a capacity of 100 kVA at the Kalibaru feeder on the PT PLN (Persero) ULP Genteng experienced overloading at WBP (88.03%) and high voltage losses. The magnitude of the load exceeds 80% of the standard transformer capacity and is in the bad category (load >= 80%) according to Table I. SE No. 0017.E/DIR/2014, related to transformer loading percentage. Meanwhile, the voltage loss of the JD267 transformer when the WBP is in Phase R is 19.05%, Phase S is 17.08%, and Phase T is 18.33%. This exceeds the voltage tolerance limit in SPLN 1:1995 that the voltage is not allowed to exceed +5% and -10% of the PLN standard voltage, namely 220 V. To handle this problem, PT. PLN (Persero) ULP Genteng carried out the installation of insert transformers by estimating load growth in the next 5 years using the Least Square method. After the addition of the insert transformer, the loading on the JD267 distribution transformer fell to 58.93% on WBP. Meanwhile, the magnitude of the JD267 transformer voltage loss when the WBP after insertion in the R Phase decreases to 0.84%, the S Phase is 1.04%, and the T Phase is 1.63%, and when the LWBP after insertion in the R Phase decreases to 0 .76%, S Phase 0.30%, and T Phase 0.6%. Based on the data above, adding an insert transformer can improve the loading percentage on the transformer and reduce voltage losses that occur at the end voltage of the transformer.